Reductions in circulating B cell subsets and immunoglobulin G levels with long-term belimumab treatment in patients with SLE. Issue 1 (7th February 2022) - Struemper, Herbert; Kurtinecz, Milena; Edwards, Lisa; Freimuth, William W; Roth, David A; Stohl, William
Abstract : Objective: To examine the long-term changes in circulating B cell subsets and IgG levels at 5+ years of continuous belimumab treatment and their correlations with efficacy and safety measures. Methods: This was a post hoc analysis of a continuation study (BEL112233; NCT00724867 ) of eligible US patients who completed the 76-week BLISS-76 Study (BEL110751; NCT00410384 ), with up to eight calendar-years of follow-up and median (IQR) belimumab exposure of 310 (209, 364) weeks. From week 76, patients initially randomised to intravenous belimumab 1 mg/kg or 10 mg/kg every 4 weeks in BLISS-76 continued to receive the same dose in the continuation study, while those initially randomised to placebo received belimumab 10 mg/kg intravenous every 4 weeks during continuation. All patients continued to receive standard SLE therapy. Biomarker data were collected, and the effects on baseline and early changes (weeks 0–24 after starting belimumab) from baseline in biomarkers on SLE Responder Index (SRI-4) and infection rate were evaluated. Results: Of the 819 patients from BLISS-76, 268 self-selecting patients entered BEL112233. Compared with baseline, B cell subset counts decreased by 40%–99% after 312 weeks (6 years), and serum IgG levels decreased by 28% after 284 weeks. Higher baseline naïve B cell counts were associated with greater SRI-4 response rates (p<0.05), whereas higher baseline SLE subset plasma and short-lived plasma B cell counts were associated with lower SRI-4 response rates (p<0.05). Elevated baseline IgG levels were associated with increased infection rates over the treatment period (p<0.05), and early greater decreases in IgG levels were associated with higher SRI-4 response rates (p<0.05). Conclusions: Belimumab treatment up to 312 weeks (6 years) resulted in substantial decreases in several circulating B cell subsets and IgG levels. Higher baseline naïve B cell counts and IgG levels were associated with improved SRI-4 response and increased infection rates, respectively.